C-kit-negative Extragastrointestinal Stromal Tumor Originating in the Mesentery Misdiagnosed as an Ovarian Tumor before Surgery - Jongryeul Lim; Myong Ki Baeg; Sangjeong Ahn; Man Ho Ha; Sun-Hye Ko; Hyuki Kwon; Jaeho Han (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Gastrointestinal stromal tumors (GISTs) are rare digestive system malignancies with extragastrointestinal stromal tumors (EGISTs) being even less. Diagnosing GISTs usually requires the identification of c-kit (CD117) expression by immunohistochemical staining. A 53-year-old woman complaining of dyspepsia was referred for the evaluation of a 1.5-cm extrinsic compression at the greater curvature of the proximal antrum. EUS revealed a multiseptated mass with positive Doppler findings. Abdominal CT showed that she harbored a large, 20-cm mass in her abdominal cavity, most likely arising from the right ovary. Surgery revealed a hypervascular tumor arising from the mesentery and attached to the gastric lesser curvature. Pathological examination revealed negativity for c-kit, but positivity for the protein “Discovered on GIST-1” (DOG1), confirming the EGIST diagnosis. Herein, we report this rare case of a c-kit-negative EGIST originating in the mesentery, which was diagnosed based on staining for DOG1.